2017
DOI: 10.4240/wjgs.v9.i12.246
|View full text |Cite
|
Sign up to set email alerts
|

Role of oral antibiotics for prophylaxis against surgical site infections after elective colorectal surgery

Abstract: Over the past few decades, surgeons have made many attempts to reduce the incidence of surgical site infections (SSI) after elective colorectal surgery. Routine faecal diversion is no longer practiced in elective colonic surgery and mechanical bowel preparation is on the verge of being eliminated altogether. Intravenous antibiotics have become the standard of care as prophylaxis against SSI for elective colorectal operations. However, the role of oral antibiotics is still being debated. We review the available… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 88 publications
0
6
0
Order By: Relevance
“…On the contrary, mechanical preparations may cause dehydration and electrolyte and metabolic derangements. Retrospective studies have suggested, however, that nonabsorbable oral antibiotics, such as neomycin, may reduce the incidence of surgical site infections (RR 0.57; 95% CI 0.43–0.76) with no effect on organ space infections or anastomotic leaks, although most studies were performed in colorectal rather than gynecologic surgery . A meta‐analysis of mechanical bowel preparation versus oral antibiotic plus mechanical bowel preparation, showed that the combination was more effective in reducing total surgical site infections (16% vs 7.2%, P <0.001).…”
Section: Early Feedingmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, mechanical preparations may cause dehydration and electrolyte and metabolic derangements. Retrospective studies have suggested, however, that nonabsorbable oral antibiotics, such as neomycin, may reduce the incidence of surgical site infections (RR 0.57; 95% CI 0.43–0.76) with no effect on organ space infections or anastomotic leaks, although most studies were performed in colorectal rather than gynecologic surgery . A meta‐analysis of mechanical bowel preparation versus oral antibiotic plus mechanical bowel preparation, showed that the combination was more effective in reducing total surgical site infections (16% vs 7.2%, P <0.001).…”
Section: Early Feedingmentioning
confidence: 99%
“…Retrospective studies have suggested, however, that nonabsorbable oral antibiotics, such as neomycin, may reduce the incidence of surgical site infections (RR 0.57; 95% CI 0.43-0.76) with no effect on organ space infections or anastomotic leaks, although most studies were performed in colorectal rather than gynecologic surgery. 12,13 A meta-analysis of mechanical bowel preparation versus oral antibiotic plus mechanical bowel preparation, 14 showed that the combination was more effective in reducing total surgical site infections (16% vs 7.2%, P<0.001). A recent ACS-NSQIP study of over 40 000 patients undergoing colorectal surgery showed that oral antibiotics alone were as good as a combination of antibiotic and mechanical bowel preparation.…”
Section: Early Feedingmentioning
confidence: 99%
“…Few studies have reported the extent to which bacterial exposure contributes to increased postoperative fever and inflammatory responses. SSIs, such as wound infections and intra‐abdominal abscesses, pose various challenges such as wound management, prolonged hospitalization, and increased medical costs 8–13 …”
Section: Introductionmentioning
confidence: 99%
“…SSIs, such as wound infections and intra-abdominal abscesses, pose various challenges such as wound management, prolonged hospitalization, and increased medical costs. [8][9][10][11][12][13] Various measures have been developed to minimize intraperitoneal contamination, including chemical preparation and anastomosis. 10 However, no studies have provided detailed information on intraoperative contamination.…”
mentioning
confidence: 99%
See 1 more Smart Citation